Chemical and Fatty acid composition of different cuts cooked or uncooked from yearling bulls fed oil sources - Oliveira, Emanuel Almeida de; Sampaio, Alexandre Amstalden Moraes; Henrique, Wignez [UNESP]; Pivaro, Thiago Martins; Rosa, Bruna Laurindo; Fernandes, Alexandre Rodrigo Mendes (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
This study evaluated the chemical and lipid composition of uncooked or cooked loin (Longissimus thoracis) and rump (Biceps femoris) in samples of 2.54 cm thick from 35 carcasses of Nellore young bulls finished in feedlot for 96 days and slaughtered at an average weight of 532.17 ± 30.25 kg and 24 months of age. The rump had the lowest level of protein and ash (18.57 and 0.90%, respectively) and the highest level of ether extract compared to loin (3.37 and 1.90%, respectively). Higher levels of cholesterol were found in rump compared to loin (40.91 e 30.93 mg 100 g-1, respectively). The uncooked loin showed lower content of saturated fatty acids and higher content of polyunsaturated fatty acids. The best values for the omega-6: omega-3 ratio was observed in the uncooked beef. In the present study, the loin was healthier due to the higher amount of polyunsaturated fatty acids compared to rump. Cooking the meat decreases the levels of polyunsaturated fatty acids, omega-3, omega-6 and the omega-6: omega-3 ratio.

Objetivou-se avaliar as diferenças na composição química e lipídica do contrafilé (Longissimus thoracis) e da picanha (Biceps femoris) in natura ou assados de bovinos alimentados com diferentes fontes de óleo. Para isto, foram utilizadas amostras, seccionadas em bifes de 2,54 cm, do contrafilé e da picanha, provenientes de 35 carcaças de tourinhos da raça Nelore, confinados por 96 dias e abatidos com peso médio de 532,17 ± 30,25 kg e 24 meses de idade. A picanha apresentou os valores mais baixos de proteína e cinzas (18,57 e 0,90%, respectivamente). No entanto, os maiores teores de extrato etéreo também foram encontrados para este corte comparado ao contrafilé (3,37 e 1,90%, respectivamente). Maiores teores de colesterol foram encontrados na picanha em relação ao contrafilé (40,91 e 30,93 mg 100 g-1, respectivamente). O contrafilé in natura apresentou menores teores de ácidos graxos saturados e maiores quantidades de ácidos graxos poli-insaturados. Para as relações dos ácidos graxos ômega-6: ômega-3, os melhores valores foram encontrados na carne in natura. O contrafilé, no presente estudo, mostrou-se mais saudável pela maior quantidade de ácidos graxos poli-insaturados que a picanha. Assar a carne diminui os teores de ácidos graxos poli-insaturados, ômega-3 e ômega-6, além da relação ômega-6: ômega-3.
Composição química e lipídica de diferentes cortes cárneos in natura ou assados de tourinhos alimentados com fontes de óleo
Keywords: Conjugated linoleic acid; Cholesterol; Ether extract; Meat cuts; Protein; Ácido linoleico conjugado; Colesterol; Extrato etéreo; Cortes cárneos; Proteína.